A review on Balanites aegyptiaca Del (desert date): phytochemical constituents, traditional uses, and pharmacological activity - Chothani, Daya L.; Vaghasiya, H. U. (Pharmacognosy Reviews)
Balanites aegyptiaca Del. (Zygophyllaceae), known as ‘desert date,’ is spiny shrub or tree up to l0 m tall, widely distributed in dry land areas of Africa and South Asia. It is traditionally used in treatment of various ailments i.e. jaundice, intestinal worm infection, wounds, malaria, syphilis, epilepsy, dysentery, constipation, diarrhea, hemorrhoid, stomach aches, asthma, and fever. It contains protein, lipid, carbohydrate, alkaloid, saponin, flavonoid, and organic acid. Present review summarizes the traditional claims, phytochemistry, and pharmacology of B. aegyptiaca Del reported in scientific literature.
Keywords: Balanites aegyptiaca; Balanitin; desert date